Implementasi Program Jum’at Berbagi Terhadap Karakter Peduli Sosial Siswa Di Mi Nurul Ulum Kayen - Musaadatul Fithriyah, Musaadatul Fithriyah; Huda, Ahmad Syaiful (Jurnal al Muta'aliyah: Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This research is motivated by the existence of a school program “Friday Sharing” to instill the social care character of students at MI Nurul Ulum Kayen Lamongan. Through the Friday Sharing program, students are expected to have high social care, sensitivity and empathy for fellow humans, friends, family and society. The purpose of this research is to find out the implementation of the Friday sharing program its impact on the social care character of students at MI Nurul Ulum Kayen Lamongan. The research method used is qualitative research with phenomenology type. Data collection techniques through observation, interviews and documentation. The results of the study obtained data, namely the implementation of the Friday Sharing program has been carried out very well at MI Nurul Ulum Kayen this is shown through the analysis of program planning and implementation shows that the Friday Sharing program is consistently carried out every week students collect gifts voluntarily, but the distribution is carried out at the end of the month on Friday. The program plays a role in fostering and developing students' high social care character, including students having an awareness to help, tolerance, empathy and noble character towards friends, teachers, family and the surrounding community.